2010
DOI: 10.3892/or_00000820
|View full text |Cite
|
Sign up to set email alerts
|

HERG K+ channel related chemosensitivity to sparfloxacin in colon cancer cells

Abstract: Abstract. Potassium channels are essential for the regulation of cell proliferation. As reported, HERG protein is overexpressed in a wide range of human tumors, including colon carcinoma. The aim of this study was to investigate the effects of antibacterial agents sparfloxacin (SPFX), a blocker of HERG channel, on HERG K + channel highly expressing colon cancer cells. Expression of HERG and apoptosis correlative proteins was examined by Western blotting. The MTT assay was used to detect the cytotoxicity of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Previous and current studies demonstrate an effect of FQs on the expression level of MMP-9 [15], suggesting that FQs could be a potential therapeutic agent for ameliorating cancer development and dissemination. We also revealed that FQ inhibits MMP-9 expression via p38 and cAMP-dependent pathways in TGF-β-and PMA-stimulated A549 cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous and current studies demonstrate an effect of FQs on the expression level of MMP-9 [15], suggesting that FQs could be a potential therapeutic agent for ameliorating cancer development and dissemination. We also revealed that FQ inhibits MMP-9 expression via p38 and cAMP-dependent pathways in TGF-β-and PMA-stimulated A549 cells.…”
Section: Discussionmentioning
confidence: 60%
“…FQs also display non-canonical mechanisms of action including, but not limited to, immunomodulatory and antitumor properties. Sparfloxacin was shown to suppress MMP-9 production by blocking HERG channel [15]. Additionally, by affecting p21/p27/p53 activities, gatifloxacin was also found to synergize the effect of gemcitabine, cisplatin as well as the broad-spectrum anticancer drugs against pancreatic cancer [16].…”
Section: Introductionmentioning
confidence: 97%
“…The hERG gene is expressed in certain cancers and has been associated with cancer development and progression (2,25). Furthermore, inhibition of the hERGrelated potassium channel has been shown to impair cell proliferation and the invasiveness of tumor cells including colorectal cancer, glioma, breast cancer, and leukemias (11)(12)(13)(14)(26)(27)(28). In this study, we identified miR-362-3p as a potential regulator of hERG expression and function in breast cancer cells.…”
Section: Discussionmentioning
confidence: 88%
“…Показано, что противоопухолевые свойства куркумина реализуются с участием АФК [122,123]. Предполагается, что куркумин вызывает АФК-индуцируемое снижение трансмембранного митохондриального потенциала, в результате активируется апоптоз [124,125]. В ряде работ показана способность куркумина через усиление внутриклеточной продукции АФК активировать аутофагию, при этом антиоксидант N-ацетилцистеин снижал, а пероксид водорода усиливал аутофагию [126,127].…”
Section: биофизика том 65 № 6 2020unclassified